The Cost of Kidney Transplant over Time. (September 2014) - Barnieh, Lianne; Yilmaz, Serdar; McLaughlin, Kevin; Hemmelgarn, Brenda R.; Klarenbach, Scott; Manns, Braden J.; ,
Background: Kidney transplant improves quality of life and survival compared with dialysis. Despite advances in immunosuppressant regimens and the prevention and treatment of acute rejection, graft survival rates have not improved significantly in the past decade. Although the clinical effectiveness of these regimens has been studied, the impact of changes over time on cost has not. Methods: Costs of kidney transplant were compared between 2 periods demarcated by a programmatic change from cyclosporine (early) to tacrolimus (late) and from nonroutine induction (early) to routine induction (late) therapy in adult patients receiving a first kidney-only transplant in Calgary, Alberta, Canada, in an 8-year period. Results: Complete costs for 3 years after transplant was available for 344 patients, including 161 adult recipients in the early period (April 1, 1998-December 31, 2001) and 183 adult recipients in the late period (January 1, 2002-March 31, 2006). The mean total 3-year cost of transplant for recipients was Can100 034 in the early period and Can144 712 in the late period largely attributed to increases in the cost of immunosuppressants ( P < .001). Conclusions: Given that the cost of transplant has increased significantly over time, the cost-effectiveness of these and other immunosuppressive regimens should be evaluated carefully.